Analisis Spasial Kemiskinan di Pulau Jawa Tahun 2022 dengan Metode Geographically Weighted Regression (GWR) - Wisly Ryan Eliezer (Universitas Sebelas Maret, 2025)
Poverty is a multifaceted problem that poses a challenge for developing countries across the world, including Indonesia. Poverty is one of the global and national obligations stated in the first Sustainable Development Goals (SDGs), namely